Analysis of relationship between ergonomics and quality: application of quality improvement throuh ergonomics in manufacturing industry - Erdinç, Oğuzhan (My University, 2006)
unknown
Keywords: Endüstri Mühendisliği; İnsan mühendisliği; Toplam Kalite Yönetimi